Jakarta Interbank Spot Dollar Rate (JISDOR) as The Reference Rate: Is It Effective? - Marwadi, Marwadi; Rokhim, Rofikoh (The Indonesian Capital Market Review, 2016)
This study analyze the influence of non-deliverable forward (NDF) and the spot rate of USD/IDR against Bank Indonesia reference rate, Jakarta Interbank Spot Dollar Rate (JISDOR). NDF which came earlier than JISDOR is used by the market participant as the reference rate. The simple method of NDF determination had a great impact on the volatility of the rupiah currency, pushing the Bank Indonesia to issue its own reference currency. JISDOR is an indication of the rates issued by Bank Indonesia as the reference rate for the foreign exchange market in domestic and overseas. The method of creating the reference rate is by weighting the average rate of real transactions through a monitoring system which is managed by the central bank. However, the question arises: what should be done by the monetary authority when there is a party outside the jurisdiction issued the NDF rate as a benchmark that may affect the domestic exchange rate of rupiah in accordance with the desired agenda of the party. We use OLS and ARCH/GARCH to see if independent variables have an influence on dependent variable. Granger Causality test is also used to observe whether there are any relations among the variables.